Generating competitiveness through interfirm co-operation: the forest industry of South Karelia and small and medium size subcontracting companies - Esa Kristian Karhu; Kalle Laine; Jyrki Ahola; Ulla Kotonen (European Regional Science Association (ERSA), 2002)
After the depression in the beginning of 1990's the regional development has been unequal in Finland, favouring some rapidly growing growth centres. The motors of the development in these centres have essentially been universities and IT-firms. At the same time when IT-based regions have been very successful many of the more traditionally oriented production areas have had problems in ensuring economic growth and balanced development of the whole region. In South-Karelia (province which lies at the South-East border of Finland) the development of the whole region is heavily related to one economic branch, forest industry. This is due to the fact that South-Karelia and it's surroundings forms production area in which the production is (even in the world scale) most intensively focused on chemical forest industry. There are four major forest industry production plants in the area: Stora-Enso / Imatra Mills, UPM-Kymmene / Kaukas Mills, Metsä-Serla / Simpele Mills and Metsä-Botnina / Joutseno Mills. In South Karelia case it is very clear that large scale enterprises have a significant role in the balanced and comprehensive development of the whole province. This applies especially to the development of economical circumstances and smaller companies in the area, but also to other aspects of human life: social, cultural and political. When we look at the structure of the companies in the area, we can determine that the situation is very biased. There are large scale companies and small companies but almost none of the medium size companies. In these economical conditions it's very clear that there might be several barriers to develop successful and multilateral co-operation between the two company-clusters, which are formulated according to company size. One of the most important barriers between the two parties is the capacity of production: The differences in production capacities hinders companies ability to develop interfirm co-operation. This study focuses on two central concepts, interfirm co-operation and competitiveness. The aim of the study was to find operation modes through which the companies in the South-Karelian region would be able to improve their competitiveness. The main objective of the study was to determine how the large scale enterprises of the woodprocessing industry in the South-Karelian region could increase their subcontracting activities among local small and medium size companies. The sub-objective of the study was to clarify the weight that those companies have on the economic structure of the South-Karelian region, and to determine the different interfirm co-operation forms that were used in the area. The methodology of the study included several characteristics of both concept analytical and constructive paradigms. The study was divided into two parts: theoretical and empirical. The theoretical part of the study forms a frame of reference in order to determine the concept of interfirm co-operation and also to classify different forms of interfirm co-operation. The theoretical part of the study was used as a basis for questionnaire and interviews. The results of the study show that interfirm co-operation is significant if the woodprocessing industry increases their subcontracting activities among the local small and medium size companies. The results show quite clearly, that interfirm co-operation can increase the competitiveness of companies. Especially useful are those modes of action which are based on long term relationships and create so called win-win situations.
Keywords: 330